Peran Pendidikan Agama Islam dalam Meningkatkan Sikap Toleransi Mahasiwa di PSDKU Universitas Brawijaya Kediri - Hasan Ansori; Suko Susilo; M. Khamim (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Islamic Religious Education (IRE) plays an essential role in shaping students character and personality based on Islamic values, including the development of tolerance toward differences. This study aims to explore and analyze the role of Islamic Religious Education in enhancing students tolerance attitudes at PSDKU Universitas Brawijaya Kediri. This research employs a qualitative approach with a descriptive method. Data were collected through observation, interviews with lecturers and students, and documentation of IRE learning activities. The findings reveal that through IRE courses, students gain a deeper understanding of universal Islamic values such as compassion, justice, and respect for diversity. These values are internalized through dialogical learning, case studies, and inclusive religious activities. The impact can be seen in students’ increasing awareness to appreciate religious differences, foster interfaith cooperation, and build a harmonious academic atmosphere. Therefore, Islamic Religious Education plays a significant role in cultivating tolerance and strengthening religious moderation within the campus environment.